From the “literary dream” to the “political dream” of the plague: Foucault (critical) reader of Camus - Chaves, Ernani (2020)
Based on the opposition between “literary dream” and “political dream”, we intend to analyze Foucault's criticism of “literature of the plague”, which includes Albert Camus's well-known book, The plague. In the end, we try to signal the fact that, taking the case of Brazil, it is pertinent to say, with Foucault, that the relations between medicine and politics constitute the background of the forms of normalization instituted during the covid 19 pandemic, but that also, despite Foucault's criticisms of the literary dream, we cannot fail to see that the transgressions of the necessary social isolation have an air of celebration and ecstasy, in a permanent game with death itself.